Ottoman Trade Policy and Activities in Europe and Asia - Meirison Alizar Sali; Desmadi Saharuddin Saharuddin; Darni Yusna Darni (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose: This discussion aims to provide an overview of Ottoman activities and policies in the field of trade and explain the factors that have led to support the economic progress and decline of this Empire.Design/Method/Approach: This discussion uses a literature study with a content study approach (content analysis) that is qualitative.Findings: Turkish Ottoman is traversed by an old trade route, which then develops into a country that is crossed by strategic trade routes from East to West with various commodities, including spices from Indonesia. One factor in the economic development of the Ottoman Empire is that the dense trade routes make this Ottoman state a political climate in Europe and Asia. Treaties and treaties and foreign capitulations are given to European countries, which only pay a 3-5% tax. To reduce Western European pressure on the Ottoman Turks in dealing with the Hapsburg family. This made traders who were 80% made up of Muslim traders drastically reduced. The treaty that was signed was like a double-edged knife for the Ottoman Turks, which was of little use in the glorious days and harmful in the weak. International trade agreements should be reviewed again in a strict manner because many of the points of the agreement are detrimental. An agreement that has eliminated much sovereignty from weak countries due to monopoly. But the Ottoman Turks had signed the deal when the Empire was at the peak of its power.Originality/Value: The contribution of this study is guidance in taking independent economic policy steps in developing trade networks and not easily giving in to foreign pressure except in emergencies.